Human-computer interaction : 19th International Conference, HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings /: 19th International Conference, HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. (2017) - Unknown
No abstract available